Lenin's political thought : theory and practice in the democratic and socialist revolution - Harding, Neil (London : Macmillan, 1983)
Bibliotheek François Vercammen
Bevat: Theory and practice in the democratic revolution ; Theory and practice in the socialist revolution
Engels
Monografie